The Hypoxia-Associated Localization of Chemotaxis Protein CheZ in Azorhizorbium caulinodans - Liu, Xiaolin; Liu, Yanan; Wang, Yixuan; Wang, Dandan; Johnson, Kevin Scot; Xie, Zhihong (Frontiers in Microbiology, 2021)
Spatial organization of chemotactic proteins is important for cooperative response to external stimuli. However, factors affecting the localization dynamics of chemotaxis proteins remain unknown. Hiremath el al. had found the polar localization of chemotaxis system II is induced by hypoxia and starvation in Vibrio cholerae. However, in V. cholerae, the chemotaxis system II is not involved in flagellum-mediated chemotaxis, and it may play other alternative cellular functions. In this study, we found that the polar localization of CheZ, a phosphatase regulating chemotactic movement in Azorhizobium caulinodans ORS571, can also be affected by hypoxia and cellular energy-status. Furthermore, the conserved phosphatase active site D165 and the C-terminus of CheZ are essential for the energy-related localization, indicating a cross link between hypoxia-related localization changes and phosphatase activity of CheZ. Three of five Aer-like chemoreceptors containing PAS domains participate in the cellular localization of CheZ. Finally, in contrast to carbon starvation, nitrogen limitation and free-living nitrogen fixation can alleviate the polar localization of CheZ. These results showed that the localization changes induced by hypoxia might be a strategy for bacteria to adapt to complex environment.